Predictors of Prolonged Hospitalization and In-Hospital Mortality After Hip Fracture: A Retrospective Study on Discharge Registry - Di Giovanni, P.; Di Martino, G.; Zecca, I. A. L.; Porfilio, I.; Romano, F.; Staniscia, T. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Hip fracture injury is one of the principal health problems affecting the elderly. Patients reporting hip fractures often show relevant comorbidities leading to prolonged hospital stay, significant complications and higher mortality rates.  This study aims to assess the risk factors associated with prolonged hospitalization after hip fracture, in-hospital mortality and transfers to other facilities.Study design. Retrospective cross-sectional study.Methods. The study considered all admissions performed between 2006 and 2015 in Abruzzo region, Italy. Logistic regression analyses were performed to evaluate odds ratios for each risk factor as predictor of in-hospital mortality, length of stay, and transfer to other facilities.Results. Age over 85 (OR=5.38) and cancer (OR=3.62) were identified as the strongest risk predictors for in hospital mortality; diabetes (OR=2.24) and heart failure (OR=1.57) were identified as predictors of prolonged length of stay and age over 85 (OR=1.38) and atrial fibrillation (OR=1.69) were identified as predictors of transfer to other facilities.Conclusions. With the rising incidence of hip fractures, identification of modifiable factors may help to reduce morbidity and mortality.